Technology-Infused Instructional Framework: Improving Pre-service Teacher Lesson Planning - Stobaugh, Rebecca; Maxwell, Margaret; Tassell, Janet (Educational (Re)naissance, 2016)
The focus of this research is to examine the impact of an instructional instrument to improve the quality of pre-service teachers’ lesson plans. The HEAT instrument focuses on four components essential to high-quality lesson plans: Higher-Order Thinking, Engaged Learning, Authentic Learning, and Technology. The research study examined a) data from elementary education classes for two semesters to measure the impact of the HEAT instrument on instructional planning during the semester and b) these pre-service teachers’ subsequent performance on the Teacher Work Sample compared to a control group of student teachers to measure the impact of the instrument on pre-service teacher performance. In the treatment group, pre-service teachers’ scores on the HEAT instrument were lower each successive semester of the study; however, during the student teaching semester the teacher candidates had higher scores on the Teacher Work Sample which measured the four components embedded in the HEAT instrument. Keywords: lesson plans; Bloom’s Taxonomy; teacher education; cognitive complexity; higher-order thinking; technology integration; authentic learning; engaged learning <!– [if gte mso 9]> 0 0 1 176 1004 California State University, Fresno 8 2 1178 14.0 96 <![endif]–><!– [if gte mso 9]> Normal 0 false false false EN-US JA X-NONE <![endif]–><!– [if gte mso 9]> <![endif]–><!– [if gte mso 10]> <![endif]–><!–StartFragment–> <!–EndFragment–>